28 STEMI in the elderly: are we treating appropriately, a large primary pci centre experience. (28th September 2016) - Cuddy, S; Sullivan, V; Mellotte, G; Yearoo, I; Crean, P; Maree, A; Murphy, R
Abstract : The elderly population (aged 80 years or older) with acute coronary syndrome is a heterogeneous group with variable frailty and differences in physiological ageing, comorbidity and functional status. Treatment of elderly patients is challenging because they are more likely than younger patients to have atypical symptoms, such as an absence of chest pain, in acute coronary syndrome. We undertook a review of the elderly population that was referred to St James Hospital as part of the National ACS programme and those that were diagnosed as an inpatient with a ST elevation MI (STEMI). We collected data from January to December 2015. We used the heartbeat database and HIPE data. We examined how many over 80's had invasive angiography and looked at key performance indicators such as ECG to door time (DDT) and ECG to reperfusion time (RT) as benchmarks of care. Our aim was to see if these patients are less likely to receive invasive treatment and if they are at a higher risk for adverse events than younger patients. Results: In 2015 there were 486 patients referred as a code STEMI to the cardiology service in SJH or diagnosed as an inpatient. The average age was 62.2 years (median 62, range 23–91 years), 25% (123) female. This included 48 patients aged 80 years and older, average age 84 (median 84, range 80–91). 22 (46%) were male with an average age of 82.6 years (median 82, range 80–88). The average female age was 84.7 years (median 85, range 80–91). The mean DDT was 89 minutes (SD 87). In SJH ED the average door to ECG time was 10 minutes (range 8–12). STEMI was the confirmed diagnosis in 38 patients; only 3 of these patients did not undergo coronary angiography. The mean RT was 105 minutes (SD 44). Six patients did not survive to discharge, a mortality rate 12.5% versus 4% in the under 80's. The DDT and RT in the under 80's were 102 and 123 minutes. There is often concern over the lack invasive care undertaken in the elderly population, that they are not managed in accordance with guideline recommendations. Our experience demonstrates that the elderly STEMI population is undergoing invasive testing and invasive therapies as per guidelines and on average within the recommended time windows. This is encouraging in an ever-expanding subgroup that is inherently higher risk. However the mortality rate was much higher in elderly, reflecting how high risk a population they are. (6-month mortality data to follow.)